Epidemiological and clinical features of 125 Hospitalized Patients with COVID-19 in Fuyang, Anhui, China. (June 2020) - Wang, Ruirui; Pan, Min; Zhang, Xiumei; Han, Mingfeng; Fan, Xiaoyun; Zhao, Fengde; Miao, Manli; Xu, Jing; Guan, Minglong; Deng, Xia; Chen, Xu; Shen, Leilei
Highlights: Do not ignore patients without certain exposure history. Pay attention to identifying asymptomatic infected patients. Certain laboratory inspection may contribute to the judgment of the severity of illness. There is no specific treatment to COVID-19 infection currently. Abstract: Objective: To investigate the epidemiological and clinical features of patients with COVID-19 in Anhui province of China. Method: In this descriptive study, we obtained epidemiological, demographic, manifestations, laboratory data and radiological findings of patients confirmed by real-time RT-PCR in the NO.2 People's Hospital of Fuyang City from Jan 20 to Feb 9, 2020. Clinical outcomes were followed up to Feb 18, 2020. Results: Of 125 patients infected SARS-CoV-2, the mean age was 38.76 years (SD, 13.799) and 71(56.8%) were male. Common symptoms include fever [116 (92.8%)], cough [102(81.6%)], and shortness of breath [57(45.6%)]. Lymphocytopenia developed in 48(38.4%) patients. 100(80.0%) patients showed bilateral pneumonia, 26(20.8%) patients showed multiple mottling and ground-glass opacity. All patients were given antiviral therapy. 19(15.2%) patients were transferred to the intensive care unit. By February 18, 47(37.6%) patients were discharged and none of patients died. Among the discharged patients, the median time of length of stay was 14.8 days (SD 4.16). Conclusion: In this single-center, retrospective, descriptive study, fever is the most common symptom. Old age, chronic underlying diseases and smoking history may be risk factors to worse condition. Certain laboratory inspection may contribute to the judgment of the severity of illness.